2020
DOI: 10.1073/pnas.1912897117
|View full text |Cite
|
Sign up to set email alerts
|

Widespread remodeling of proteome solubility in response to different protein homeostasis stresses

Abstract: The accumulation of protein deposits in neurodegenerative diseases has been hypothesized to depend on a metastable subproteome vulnerable to aggregation. To investigate this phenomenon and the mechanisms that regulate it, we measured the solubility of the proteome in the mouse Neuro2a cell line under six different protein homeostasis stresses: 1) Huntington’s disease proteotoxicity, 2) Hsp70, 3) Hsp90, 4) proteasome, 5) endoplasmic reticulum (ER)-mediated folding inhibition, and 6) oxidative stress. Overall, w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
69
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(76 citation statements)
references
References 69 publications
6
69
0
Order By: Relevance
“…Proteome‐wide mass spectrometry‐based studies have been previously used to characterize aggregation‐prone proteins in different organisms and conditions. These include, for example, aging nematode (David et al , 2010; Reis‐Rodrigues et al , 2012; Walther et al , 2015), mice expressing disease‐causing mutant of huntingtin protein (Hosp et al , 2017), mice cells exposed to different stress conditions (Sui et al , 2020), and yeast under chemical or heat stress (Ibstedt et al , 2014; O'Connell et al , 2014; Wallace et al , 2015; Weids et al , 2016). Although these studies involved quite different organisms and conditions, some similarities could be found.…”
Section: Introductionmentioning
confidence: 99%
“…Proteome‐wide mass spectrometry‐based studies have been previously used to characterize aggregation‐prone proteins in different organisms and conditions. These include, for example, aging nematode (David et al , 2010; Reis‐Rodrigues et al , 2012; Walther et al , 2015), mice expressing disease‐causing mutant of huntingtin protein (Hosp et al , 2017), mice cells exposed to different stress conditions (Sui et al , 2020), and yeast under chemical or heat stress (Ibstedt et al , 2014; O'Connell et al , 2014; Wallace et al , 2015; Weids et al , 2016). Although these studies involved quite different organisms and conditions, some similarities could be found.…”
Section: Introductionmentioning
confidence: 99%
“…Proteome-wide mass spectrometry-based studies have been previously used to characterize aggregation-prone proteins in different organisms and conditions. These include, for example, aging nematode [7][8][9], mice expressing disease-causing mutant of huntingtin protein [10], mice cells exposed to different stress conditions [11] and yeast under chemical or heat stress [12][13][14][15]. Although these studies involved quite different organisms and conditions, some similarities could be found.…”
Section: Introductionmentioning
confidence: 99%
“…Of these, 9 proteins were found in our list of 55 proteins significantly enriched in Httex1Q 97 inclusions (Pcbp1, Dnaja2, Sgta, Picalm, Hgs, Clint1, Ubqln1, Ubqln2 and Dnajb1) ( Fig 4A). When we also considered proteins that were identified in either inclusion (full list of proteins in S2 Table), which are therefore candidate proteins that are recruited to both inclusion types, we found a further 7 proteins that overlapped with the previous published data from Sui et al [73]. Analysis of the protein:protein interaction networks by STRING analysis revealed two robust networks within these proteins that map onto gene ontology enrichments for mechanisms related to protein quality control including positive regulation of proteolysis (GO:0045862; FDR of 0.0029), positive regulation of ERAD pathway (GO:1904294; FDR of 8.76E-05), heat shock protein binding (GO:0031072; FDR of 2.43E-06) and protein folding (GO:0006457; FDR of 0.00034) ( Fig 4B and full list of GO terms in S6 Table).…”
Section: Plos Onementioning
confidence: 63%
“…We also examined the overlap with our previously reported changes in solubility of whole cell proteome before versus after inclusions had formed [73] (Fig 4A). In that dataset (Sui et al [73]) we observed 25 proteins that significantly decreased in solubility as cells expressing Httex1Q 97 shifted from a dispersed unaggregated state to forming inclusions [73] (S6 Table). Of these, 9 proteins were found in our list of 55 proteins significantly enriched in Httex1Q 97 inclusions (Pcbp1, Dnaja2, Sgta, Picalm, Hgs, Clint1, Ubqln1, Ubqln2 and Dnajb1) ( Fig 4A).…”
Section: Plos Onementioning
confidence: 93%